1999
DOI: 10.1001/archfami.8.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Testosterone Replacement Therapy in Men

Abstract: Testosterone plays an essential role in the development of the normal male and in the maintenance of many male characteristics, including muscle mass and strength, bone mass, libido, potency, and spermatogenesis. Androgen deficiency occurs with disorders that damage the testes, including traumatic or surgical castration (primary testicular failure) or disorders in which the gonadotropin stimulation of the testes is reduced (hypogonadotropic hypogonadism). The clinical manifestations of androgen deficiency depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(11 citation statements)
references
References 40 publications
(49 reference statements)
0
9
0
2
Order By: Relevance
“…17,18 The mechanisms that mediate testosterone's skeletal effects remain incompletely understood. However, in our study, we found no correlation between admission testosterone levels and bone density despite the fact that the older males had lower admission testosterone levels and more bone loss than the younger males.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The mechanisms that mediate testosterone's skeletal effects remain incompletely understood. However, in our study, we found no correlation between admission testosterone levels and bone density despite the fact that the older males had lower admission testosterone levels and more bone loss than the younger males.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of androgen deficiency in men may include decreased muscle mass and strength, increased fat mass, decreased hematocrit, decreased libido, erectile dysfunction, infertility, osteoporosis, anxiety, irritability, insomnia, depressed mood. Androgen replacement therapy with testosterone has been proposed to be a safe and effective treatment for testosterone deficiency (Sternbach, 1998;Winters, 1999). However, there are only a limited number of testosterone replacement studies with sometimes conflicting results (Sih et al, 1997;Tenover, 1992;Snyder et al, 1999a,b).…”
Section: Hormone Replacement Therapy In Humansmentioning
confidence: 99%
“…1 Testosterone levels decline gradually with age, and testosterone deficiency can cause significant morbidity and substantial reduction in quality of life.…”
Section: Introductionmentioning
confidence: 99%